STUDY OF CRUDE EXTRACTS FROM CASSIA SIEBERIANA ROOT BARK AND KHAYA GRANDIFOLIOLA TRUNK BARK: PHYTOCHEMICAL SCREENING, QUANTITATIVE ANALYSIS AND RADICAL SCAVENGING ACTIVITY - Traore, Lancine; Bekro, Yves-alain; Pirat, Jean-luc; Mamyrbeva-bekro, Janat Akhanovna (International Journal of Current Pharmaceutical Research, 2015)
Objective: Cassia sieberiana and Khaya grandifoliola are two plants commonly used in traditional medicine in Côte d’Ivoire. Photochemical screening of crud extract obtained from C. sieberiana root bark and K. grandifoliola trunk bark revealed the presence of alkaloids, sterols, terpenes, polyphenols, flavonoids, coumarins, tannins, reducing sugars, glycosides, carbohydrates, cardiac glycosides and saponins. Methods: Quantitative analysis was screened in C. sieberiana root bark and K. grandifoliola trunk bark. Results: The results respectively showed high concentrations of total phenols (225.57±7.57 and 186.75±12.76 μgGAE/mg), total flavonoids (64.70±5.25 and 117.88±8, 68 μgQE/mg) and total tannins (170.60±5.85 and 39.96±1, 58 μgTAE/mg). The antioxidant activity of the glycosides extracts CS1, KG1 and their corresponding aglycones CS2, KG2 of these plants has been studied by scavenging free radicals by DPPH and that, compared with L-ascorbic acid (vitamin C, IC50 = 0.07 µg/ml). IC50 values of CS1 (2.69 µg/ml), KG1 (3.16 µg/ml) and CS2 (1.30 µg/ml), KG2 (0.726 µg/ml) showed that the aglycones are clearly more effective than the glycosides. Conclusion: Qualitative analysis of Cassia sieberiana root bark and Khaya grandifoliola trunk bark showed a presence of a variety of secondary metabolites in these plants, when the quantitative analysis concludes that they contain phenolic compounds, flavonoids and tannins to varied contents.